Comparative Study of Mesh Fixation with Non-Absorbable versus Delayed Absorbable Monofilament Suture in Lichtenstein Tension-Free Hernioplasty with Respect to Chronic Postoperative Pain - Tahir, Sana; Jahangir, Maha; Dhomeja, Vishal; Naseer, Shafaq; Jokhio, Sharmeen; Sheikh, Kainat (Biological and Clinical Sciences Research Journal, 2025)
Inguinal hernia repair is among the most frequently performed surgical procedures globally. The Lichtenstein tension-free mesh technique remains the gold standard; however, chronic postoperative groin pain continues to impact patients' quality of life. The influence of suture absorbability on long-term postoperative pain remains inadequately explored. Objective: Inguinal hernia repair is common worldwide. The Lichtenstein tension-free mesh technique is standard, but chronic postoperative groin pain affects quality of life. Evidence on the impact of suture absorbability on long-term pain is limited. This study compared postoperative pain after mesh fixation with absorbable Vicryl versus non-absorbable Prolene sutures. Methods: In a prospective, non-randomized cohort study at Civil Hospital Karachi, 300 adults undergoing elective, unilateral, primary Lichtenstein hernia repair were alternately assigned to Vicryl (Group A, n=150) or Prolene (Group B, n=150). Pain was measured using the Visual Analog Scale (VAS; 0–10) preoperatively, 24 hours, 7 days, 1, 3, and 6 months postoperatively. Chronic pain was defined as pain ≥3 months; VAS <3 At six months, clinical efficacy was predefined. Statistical analyses used Mann–Whitney U and Chi-square tests. Results: Baseline characteristics were comparable. Early postoperative pain at 24 hours and 7 days did not differ (p>0.05). At 1, 3, and 6 months, Group A had significantly lower pain scores than Group B (p<0.001). At six months, 97.3% of Vicryl patients were pain-free (VAS <3) versus 79.3% of Prolene patients (p<0.001). Conclusion: Absorbable Vicryl sutures in Lichtenstein hernia repair reduce intermediate- and long-term postoperative pain compared to non-absorbable Prolene, without affecting operative time. Use of absorbable sutures may improve patient comfort and reduce healthcare burden.